2000
DOI: 10.1094/phyto.2000.90.9.1018
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Associated with Resistance to Gray Leaf Spot of Corn

Abstract: The susceptible parent FR1141, the resistant parent 061, the F1 cross, and 301 families selfed once from backcrosses to the susceptible parent were evaluated for gray leaf spot (GLS) severity for two years in Urbana, IL, and one year in Andrews, NC. Linkage between ear height and GLS severity was suspected. Therefore, plant height characteristics were noted for two years in Urbana, IL. Eighty-six polymorphic probes were used to construct a random fragment length polymorphism linkage map, and the presence, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
44
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 38 publications
12
44
1
1
Order By: Relevance
“…Finally, the map position of the GST gene identified in this study colocalized with or immediately flanked quantitative trait loci for SLB, GLS, and NLB identified in previous studies [compare position 298 cM on chromosome 7 with quantitative trait loci (4)]. A closer examination suggested that these resistance loci were not attributable to the effect of this GST gene; based on our SNP data, each of the significantly associated GST SNPs identified in this study (above and below) was invariant among the five biparental population parents used in previous studies (33)(34)(35)(36)(37)(38). Alternatively, other GST alleles that are undetectable in our study could underlie functional variation at these quantitative trait loci.…”
Section: Resultssupporting
confidence: 68%
“…Finally, the map position of the GST gene identified in this study colocalized with or immediately flanked quantitative trait loci for SLB, GLS, and NLB identified in previous studies [compare position 298 cM on chromosome 7 with quantitative trait loci (4)]. A closer examination suggested that these resistance loci were not attributable to the effect of this GST gene; based on our SNP data, each of the significantly associated GST SNPs identified in this study (above and below) was invariant among the five biparental population parents used in previous studies (33)(34)(35)(36)(37)(38). Alternatively, other GST alleles that are undetectable in our study could underlie functional variation at these quantitative trait loci.…”
Section: Resultssupporting
confidence: 68%
“…Several mapping studies have examined both maturityrelated and disease-related traits for maize necrotrophic diseases in the same populations (Bubeck et al 1993;Jung et al 1994;Jiang et al 1999;Clements et al 2000;Carson et al 2004;. While none showed a strong correlation between the two traits, colocalization of disease QTL and maturity-related QTL and/or significant correlations between disease resistance and time to anthesis were observed in some of these studies, especially for studies on gray leaf spot-resistance QTL.…”
Section: Mo17 Advanced Intercross Recombinant Inbred Line Population mentioning
confidence: 99%
“…Quantitative resistance to grey leaf spot leads to prolonged latent and incubation periods, reduced infection rates, sporulation capacity and the number of lesions (Beckman & Payne 1982;Carson & Goodman 2006). The resistance factors have been mapped to three different chromosomes at least, with some of the quantitative trait loci (QTL) consistently expressed across environments (Clements et al 2000;Gordon et al 2004). Carson and Goodman (2006) reported that resistance to grey leaf spot in maize appears to be equally effective against both type I and type II of C. zeae-maydis and that aggressive isolates, regardless of which sibling species of C. zeae-maydis, should be used to select for grey leaf spot resistance in field trials.…”
Section: Grey Leaf Spot Caused By Cercospora Zeae-maydismentioning
confidence: 99%